An Examination of Self-Concept and Consumptive Behavior: The Phenomenon of Online Shopping - Yufita Jasmine; Cempaka Putrie Dimala; Ananda Saadatul Maulidia (Psikostudia : Jurnal Psikologi, 2024)
One of the basic elements that influences consumer behavior is self-concept. Online shopping is most often done by adolescents aged 18-21 years. This study aims to examine the influence of self-concept on consumer behavior in online shopping among adolescents in Karawang Regency. Participants in this study were adolescents aged between 12 and 21 years totaling 204 and using accidental sampling for this study. The Self-Concept Scale (PSC) contains eighteen valid questions on the Self-Concept Scale (reliability α = 0.942) and the Consumptive Behavior Scale twenty-three valid questions on the Consumptive Behavior Scale (reliability α = 0.948). Specifically, self-concept has an impact on consumer behavior (sig 0.000 <0.05). The regression coefficient of the self-concept variable is -0.155 which means there is a negative influence between self-concept and consumer behavior in online shopping among adolescents in Karawang Regency. Adolescents who have a high and positive self-concept tend to be wiser in shopping, while those with a low self-concept are more susceptible to external influences and more likely to engage in excessive consumer behavior.Salah satu elemen mendasar yang mempengaruhi perilaku konsumtif adalah konsep diri. Belanja online paling sering dilakukan oleh remaja yang berada di rentang usia 18-21 tahun. Penelitian ini bertujuan untuk menguji pengaruh konsep diri terhadap perilaku konsumtif dalam berbelanja online pada remaja di Kabupaten Karawang. Partisipan dalam penelitian ini adalah remaja yang berusia antara 12 hingga 21 tahun yang berjumlah 204 dan menggunakan accidental sampling untuk penelitian ini. Skala Konsep Diri (PSC) terdapat delapan belas pertanyaan yang valid pada Skala Konsep Diri (reliabilitas α = 0,942) dan Skala Perilaku Konsumtif dua puluh tiga pertanyaan yang valid pada Skala Perilaku Konsumtif (reliabilitas α = 0,948). Secara khusus, konsep diri memiliki dampak pada perilaku konsumtif (sig 0.000<0.05). Koefisien regresi variabel konsep diri adalah -0.155 yang berarti ada pengaruh negatif antara konsep diri terhadap perilaku konsumtif dalam berbelanja online pada remaja di Kabupaten Karawang. Remaja yang memiliki konsep diri yang tinggi dan positif cenderung lebih bijaksana dalam berbelanja, sementara mereka yang memiliki konsep diri yang rendah lebih rentan terhadap pengaruh eksternal dan lebih cenderung terlibat dalam perilaku konsumtif yang berlebihan.